Children's Literature in Translation : Texts and Contexts - McMartin, Jack; Coillie, Jan van (Translation, interpreting and transfer ;, 2020)
For many of us, our earliest and most meaningful experiences with literature occur through the medium of a translated children's book. This volume focuses on the complex interplay that happens between text and context when works of children's literature are translated: what contexts of production and reception account for how translated children's books come to be made and read as they are? How are translated children's books adapted to suit the context of a new culture? Spanning the disciplines of Children's Literature Studies and Translation Studies, this book brings together established and emerging voices to provide an overview of the analytical, empirical and geographic richness of current research in this field and to identify and reflect on common insights, analytical perspectives and trajectories for future interdisciplinary research. This volume will appeal to an interdisciplinary audience of scholars and students in Translation Studies and Children's Literature Studies and related disciplines. It has a broad geographic and cultural scope, with contributions dealing with translated children's literature in the United Kingdom, the United States, Ireland, Spain, France, Brazil, Poland, Slovenia, Hungary, China, the former Yugoslavia, Sweden, Germany, and Belgium.